Work ability in prostate cancer survivors after radical prostatectomy. (3rd March 2016) - Dahl, Sigrun; Cvancarova, Milada; Dahl, Alv A.; Fosså, Sophie D.
Abstract: Objective : The aim of this study was to evaluate work ability (WA) after radical prostatectomy (RP) in prostate cancer survivors, in relation to post-RP urinary leakage (UL) and adjuvant or salvage pelvic radiation therapy (RT) and/or hormone therapy (HT). Methods : Patients for this cross-sectional study were selected from two surveys on post-RP adverse effects and WA. All participated in the workforce. Using EPIC-50/26, UL was defined as daily use of at least one pad. Data on RT were obtained from the Cancer Registry of Norway. WA, measured by the Work Ability Score (WAS), was categorized into "excellent", "good" or "moderate/poor". Multinomial logistic regression analyses assessed associations between WA and selected variables. p values below 0.05 were considered statistically significant. Results : Of 563 patients, 18% had received post-RP RT and/or HT. Compared to the "excellent" WAS category, such treatment was significantly associated with belonging to the "good" or "moderate/poor" category. Patients with UL (30%) were more than twice as likely to report a "moderate/poor" WAS than those without UL. Age above 65 years, less than 3 years since RP and co-morbidity were additional factors associated with increased risk of reporting a lower WAS. Half of the patients rated their current WA as "very good" with respect to the physical or mental demands of their work. Conclusion : Increasing age, UL, co-morbidity and time since RP are associated with decreasing post-RP WA. Without specifying the individual therapy, post-RP oncological treatment seems to have an additional negative effect, warranting consideration of patients' work plans when considering post-RP oncological treatment.